Outcomes of Sjögren's versus non-Sjögren's related dry eye in a longitudinal, tertiary clinic-based sample. - David Cui; Priya Mathews; Gavin Li; Shanna VanCourt; Esen Akpek (PLoS ONE)
Purpose To assess the long-term treatment outcomes of dry eye in patients with and without underlying primary Sjögren's syndrome (SS). Design Retrospective longitudinal cohort. Methods SS and non-SS dry eye patients with clinic visits for a minimum of 5 consecutive years at a tertiary, dedicated dry eye clinic were included. Electronic health records were reviewed to collect data regarding demographics, objective dry eye parameters, treatments utilized at baseline and final visit, and corneal complications observed during follow-up. Results Two hundred and two patients (101 SS and 101 randomly selected non-SS), with a mean follow-up of 7.1 years were included. At baseline, mean conjunctival lissamine green staining score was 2.9 and mean corneal fluorescein staining score was 2.0. At last visit, notable improvement in staining score for cornea (-1.1, P < .001) and conjunctiva (-1.8, P < .001) was seen equally in both dry eye groups. Most patients (88.1%) had an escalation of treatment by the final visit, with similar rates in both groups (P = .51). Half (48.9%) of the patients had no conjunctival staining, and a third (34.4%) had no corneal staining at their last visit. Twenty (9.9%) patients experienced a vision-threatening corneal complication, including ulcers and melt, with no difference in occurrences between the groups (P = .64). Conclusions The majority of patients in this longitudinal, tertiary clinic-based sample demonstrated improvement in their ocular surface staining score by the final visit with escalation in treatment. Treatments used, improvement achieved, and corneal complication rates leading to loss of vision were similar in both SS and non-SS dry eye groups.